THE ROLE OF COMMUNITY IN DESIGN AND EVALUATION SERVICE REGIONAL DIGITAL PUBLIC AT THE COMMUNICATION AND INFORMATICS OFFICE REGENCY SOUTH BUTON - Sry Mayunnita; Juanda Nawawi; Andi Lukman Irwan (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to analyze the role of citizens in the design and evaluation of digital public services in South Buton Regency as part of the implementation of e-government policy. A qualitative descriptive approach was applied using a case study method at the Department of Communication and Informatics of South Buton Regency. Data were collected through in-depth interviews, participatory observation, and document analysis, involving purposively selected informants such as government officials, digital service users, and community representatives. The findings reveal that public participation significantly contributes to the relevance, effectiveness, and legitimacy of digital public services. Citizens’ engagement is manifested through consultative, collaborative, and co-creation models that strengthen transparency and government accountability. The study concludes that the success of digital transformation depends on digital literacy, inclusive infrastructure, and sustainable participatory mechanisms, offering policy implications for strengthening citizen-centered digital governance at the local level.